Potential drug interactions analysis of COVID-19 patients at a hospital in West Java - Larasati Arrum Kusumawardani; Nisa Maria; Yumna Nabila Fanani (Universitas Islam Indonesia, 2021)
Background: Treatment guidelines of COVID-19 are changing continuously by involving many off-label and various symptomatic or supportive drugs. The use of these various drugs might increase the patient’s risk of developing drug interactions.Objective: The study aimed to analyze potential drug-drug interactions in COVID-19 inpatients and the correlated factors.Method: A cross-sectional study was conducted in a hospital by using inpatients admitted from August-December 2020. Potential drug-drug interaction was analyzed by using Lex-Interact® software.Results: From 107 patients, the majority of them are in moderate severity-degree (98.1%), having comorbidities (93.5%), and polypharmacy (98.1%). The average of potential drug interactions was 8.47±8,04, with most of the interaction in risk rating C-monitor therapy. Major potential drug interactions found were prolongation of QT interval and disturbance of drug absorption in the gastrointestinal tract. A positive correlation occurred between drug interactions found and comorbidity (r=0.436), number of drugs per prescription (r=0.674), and length of stay (r=0.222)Conclusions: COVID-19 patient is at risk for developing potential drug interactions that can affect the patient's physiological condition and reduce drug effect. It is necessary to manage the medication schedule, therapy modification, administration route changing, dosage adjustment, and monitoring of effects that might occur because of the drug interactions.Keywords: drug interaction, COVID-19, inpatient, correlated factor IntisariLatar belakang: Tatalaksana pengobatan COVID-19 terus berkembang dengan melibatkan berbagai jenis obat off-label dan berbagai obat terapi simptomatik ataupun suportif. Penggunaan berbagai jenis obat ini membuat pasien berisiko mengalami interaksi obat.Tujuan: Penelitian ini bertujuan untuk menganalisis potensi interaksi antar obat yang dapat terjadi pada pasien COVID-19 rawat inap serta faktor yang mempengaruhinya.Metode: Penelitian dilakukan dengan desain cross-sectional menggunakan sampel pasien rawat inap di rumah sakit pada periode Agustus-Desember 2020. Analisis potensi interaksi antar obat dilakukan dengan menggunakan Lexi-Interact®Hasil: Sebanyak 107 sampel pasien didapatkan mayoritas dalam tingkat keparahan sedang (98,1%), memiliki komorbid (93,5%), dan polifarmasi (98,1%). Rata-rata jumlah potensi interaksi obat yang dialami adalah 8,47± 8,04 dengan tingkat interaksi paling banyak pada kategori C (pantau terapi) (54,61%). Potensiinteraksi obat mayor yang banyak ditemukan adalah adanya perpanjangan pada interval QT serta gangguan absorpsi obat di saluran cerna. Terdapat korelasi positif antara potensi interaksi obat dengan faktor komorbid (r=0,436), jumlah obat per resep (r=0,674), serta lama rawat inap (r= 0,222).Kesimpulan: Pasien COVID-19 memiliki risiko tinggi untuk mengalami potensi interaksi obat yang dapat mempengaruhi kondisi fisiologis pasien dan mengurangi efek terapi obat. Maka dari itu, perlu dilakukan pengaturan waktu minum, modifikasi terapi, perubahan rute pemberian, penyesuaian dosis, serta pemantauan efek obat yang mungkin muncul akibat interaksinya.Kata kunci : interaksi obat, COVID-19, rawat inap, faktor yang mempengaruhi